Implant Preference and Clinical Outcomes of Patients with Staged Bilateral Total Knee Arthroplasty: All-Polyethylene and Contralateral Metal-Backed Tibial Components - Nachtnebl, Luboš; Apostolopoulos, Vasileios; Mahdal, Michal; Pazourek, Lukáš; Brančík, Pavel; Valoušek, Tomáš; Boháč, Petr; Tomáš, Tomáš (Journal of clinical medicine, 2023)
Numerous studies have compared metal-backed components (MBTs) and all-polyethylene tibial components (APTs), but none of them specifically analysed the clinical results and the overall patient preference in patients who had undergone a staged bilateral knee replacement. The purpose of this study is to compare clinical results, perceived range of motion, and overall implant preference among patients who had undergone staged bilateral knee replacement with an APT and contralateral knee replacement with MBTs. A dataset of 62 patients from a single centre who underwent staged bilateral TKA between 2009 and 2022 was selected and retrospectively analysed. Tibial component removal was performed in three knees overall, all of which had MBTs. The mean measured Knee Score (KS) of knees with APTs was 78.37 and that of contralateral knees with MBTs was 77.4. The mean measured Function (FS) of knees with APTs was 78.22, and that of contralateral knees with MBs was 76.29. The mean flexion angle of knees with APTs was 103.8 and that for knees with MBTs was 101.04 degrees. A total of 54.8% of the patients preferred the knee that received APTs over contralateral MBTs. In our cohort, TKA with an APT in one knee and an MBT in the contralateral knee recorded similar clinical results and perceived ranges of motion. Patients in general preferred the knee that received an APT over contralateral knee with an MBT.